2018
DOI: 10.4103/ijmy.ijmy_161_17
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid levels in patients on antituberculosis drugs in the southwest Region of Cameroon

Abstract: Hyperuricemia is associated with ATDs, with treatment duration being a significant factor. The disorder should be closely monitored, especially during the intensive phase of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, weak correlations were found between INH and RMP and INH and EMB in our work. A large number of previous studies have shown that anti-TB drugs can affect UA metabolism in humans, which could result in Frontiers in Pharmacology frontiersin.org elevated blood UA (Louthrenoo et al, 2015;Thumamo Pokam et al, 2018;Ha et al, 2019). We also found that UA was an independent influencing factor of the PZA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, weak correlations were found between INH and RMP and INH and EMB in our work. A large number of previous studies have shown that anti-TB drugs can affect UA metabolism in humans, which could result in Frontiers in Pharmacology frontiersin.org elevated blood UA (Louthrenoo et al, 2015;Thumamo Pokam et al, 2018;Ha et al, 2019). We also found that UA was an independent influencing factor of the PZA concentration.…”
Section: Discussionmentioning
confidence: 99%